PENGARUH QUALITY OF WORK LIFE TERHADAP MOTIVASI KERJA DAN KEPUASAN KERJA KARYAWAN - Ni Luh Putu Surya Astitiani; Ida Bagus Ketut Surya (Faculty of Economics and Business Udayana University, 2016)
This study aims to determine the effect on the Quality of Work Life Work Motivation and Job Satisfaction. The study was conducted at the Swastika Bungalows Sanur, with a sample of 60 employees who were taken withsaturated or census sampling method. Data analysis technique used is the technique of path analysis (path analysis). The results showed that the higher the Quality Of Work Life applied by the company, the higher employee motivation that impact on enhancing employee satisfaction with the results of path analysis showed that motivation positive effect in mediating the effect of Quality Of Work Life on employee job satisfaction so , the results of this study can serve as a reference for the company to improve the welfare of employees through increased job security, giving freedom to employees, and increased the incentive for employees to have an impact on increasing the productivity of the company.